2013
DOI: 10.1177/0963662512469916
|View full text |Cite
|
Sign up to set email alerts
|

Measuring mumbo jumbo: A preliminary quantification of the use of jargon in science communication

Abstract: Leaders of the scientific community encourage scientists to learn effective science communication, including honing the skill to discuss science with little professional jargon. However, avoiding jargon is not trivial for scientists for several reasons, and this demands special attention in teaching and evaluation. Despite this, no standard measurement for the use of scientific jargon in speech has been developed to date. Here a standard yardstick for the use of scientific jargon in spoken texts, using a compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 34 publications
(43 reference statements)
3
56
0
2
Order By: Relevance
“…This statement is in line with findings from other authors and recommendations in handbooks for popular science journalists 2 . Generally, Sharon/Baram-Tsarabi (2014) show that the amount of terms (or jargon, as they prefer) in popular science communication (esp. in TED Talks) is reduced in comparison to the intra-scientific communication between experts.…”
Section: State Of the Art: Terms In Popular Science Communicationmentioning
confidence: 99%
“…This statement is in line with findings from other authors and recommendations in handbooks for popular science journalists 2 . Generally, Sharon/Baram-Tsarabi (2014) show that the amount of terms (or jargon, as they prefer) in popular science communication (esp. in TED Talks) is reduced in comparison to the intra-scientific communication between experts.…”
Section: State Of the Art: Terms In Popular Science Communicationmentioning
confidence: 99%
“…There are, however, many instances where physicists speak to non-experts about various issues related to science, including current research topics. In these cases, using the same strategies and levels of scientific jargon as with fellow physicists may not be appropriate, and is discouraged [13]. Researchers have been studying jargon and strategies used by scientists when communicating to different groups.…”
Section: Communication Frameworkmentioning
confidence: 99%
“…Kapon et al have identified 4 elements of language (analogies, narrative elements, organization, and content choices) that are used in popular public lectures by physics professors [12]. Additionally, Sharon and Baram-Tsabari have quantified jargon by comparing language used in academic seminars and TED Talks to databases of common science and everyday words [13]. We draw from this body of literature as the basis for our analysis of scientific communication by physics students to K-8 children in an afterschool program.…”
Section: Communication Frameworkmentioning
confidence: 99%
“…Science communication has received significant attention since the beginning of the twenty‐first century in an effort to improve PUS hand‐in‐hand with improving the public's positive attitudes towards science (Sharon & Baram‐Tsabari, ; Short, ). As PUS refers to the ‘ability of individuals to read and understand information about basic scientific constructs, including some technological constructs’ (Miller, , p. 812), it is oriented to the product , or outcome, of science communication.…”
Section: Introductionmentioning
confidence: 99%